The spectrum of dermatological disorders among primary school children in Dar es Salaam - Mgonda Yassin M; Komba Ewaldo V (BMC, 2010)
Abstract Background Dermatologic disorders are common in many countries but the spectrum varies greatly. Many studies have reported a significant burden of skin diseases in school children. The objective of this study was to determine the current spectrum of dermatological disorders in primary school children in Dar es Salaam city. Methods Primary school children were recruited by multistage sampling. Detailed interview, dermatological examination and appropriate laboratory investigations were performed. Data was analyzed using the 'Statistical Package for Social Sciences' (SPSS) program version 10.0 and EPI6. A p-value of < 0.5 was significant. Results A total of 420 children were recruited (51% males; mean age 11.4 ± 2.8 years; range 6-19 years). The overall point prevalence of any skin disorder was 57.3% and it was 61.9% and 52.6% in males and females respectively (p = 0.05). Infectious dermatoses accounted for 30.4% with superficial fungal infections (dermatophytoses and pityriasis versicolor) being the commonest (20%). Dermatophytoses were diagnosed in 11.4% (48/420); the prevalence in males and females being 12.6% and 10.1% respectively (p = 0.41) and higher (21.8%) in the age-group 6-10 years (p = 0.045). Fungal cultures were positive in 42/48 children (88%). All three dermatophyte genera were isolated. Tinea capitis was the commonest disease among culture-positive dermatophytoses (30/42; 71.4%) with an overall prevalence of 7.1% (30/420) followed by tinea pedis (11/42; 26.1%) whose overall prevalence was 2.6%. Microsporum canis was common in tinea capitis (14/30; 46.7%) followed by Trichophyton violaceum (6/30; 20%). Trichophyton rubrum was common in tinea pedis (5/11; 45.5%). Thirty six children (8.6%) had pityriasis versicolor which was more prevalent (6/27; 22.l2%) in the age group 16-19 years (p = 0.0004). The other common infectious dermatoses were pyodermas (4%) and pediculosis capitis (3.6%). Common non-infectious dermatoses were: acne vulgaris (36.4%), non-specific dermatoses (10.7%), non-specific ulcers (5%) and atopic eczema (2.6%). Rare conditions (prevalence < 1%) included: vitiligo, alopecia areata and intertrigo. The majority of the affected children (67.2%) did not seek any medical assistance. Conclusions Skin disorders are common in primary school children; infectious dermatoses are still rampant and many children do not seek medical assistance.